Reproductive Factors and Incidence of Endometrial Cancer in U.S. Black Women - Sponholtz, Todd R. (Cancer Causes Control, 2017)
PURPOSE: Previous studies have shown that reproductive history is a strong determinant of endometrial cancer risk among white women. Less is known about how reproductive history affects endometrial cancer risk among black women, whose incidence and mortality differ from white women. We investigated the associations of age at menarche, parity, timing of births, and menopausal age with endometrial cancer in the Black Women’s Health Study, a prospective cohort study. METHODS: Every 2 years from 1995 to 2013, 47,555 participants with intact uteri at baseline in 1995 completed questionnaires on reproductive and medical history, and lifestyle factors. Self-reported cases of endometrial cancer were confirmed by medical record, cancer registry, or death certificate when available. Cox proportional hazards regression was used to estimate multivariable incidence rate ratios (IRR) and 95% confidence intervals (CI). RESULTS: During 689,501 person-years of follow-up, we identified 300 incident cases of endometrial cancer. The strongest associations with endometrial cancer were found for early age at menarche (<11 vs. 12–13 years: IRR: 1.82, 95% CI: 1.31, 2.52), and later age at first birth (≥30 vs. <20 years: IRR: 0.26, 95% CI: 0.13, 0.50). Parous women were less likely than nulliparous women to develop endometrial cancer (IRR: 0.77, 95% CI: 0.57, 1.05), but there was little evidence of a dose-response relation for number of births. CONCLUSION: Associations between reproductive factors and endometrial cancer among black women were generally consistent with those in studies of white women.